Selection of the Best Method of Soil Phosphorus Test for Tomato (Solanum lycopersicum L.) on Andisols - Gunawan, Endang; Susila, Anas D; Santosa, Edi; Sutandi, Atang (Departemen Agronomi dan Hortikultura, 2025)
Determination of recommendations for phosphorus (P) based on soil tests for tomato in Andisol has not been done in Indonesia. Beginning with the making of P soil status in IPB Research Station Pasirsarongge Cianjur and followed by a correlation test in PKHT IPB greenhouse Tajur Bogor West Java, from November 2015 to April 2016. The objective was to select the best extraction method of P Andisols for tomato. This research used a single-location approach; with a randomized block design. The treatments were soil P status by application of phosphoric acid solution (H3PO4) with five rates of P : 0, ¼,X, ½X, ¾X, and X. X was the P rate of 2240 kg P ha-1 was applied to achieve maximum P concentration in the soil. H3PO4 solution was applied to the bed surface and incubated for 4 months to obtain different P nutrient statuses. A study of the Correlation test conducted in the greenhouse used the 4 month incubated soil. Analysis of soil P using five extraction methods: Bray 1 (HCl 5N), HCl 25%, Morgan Wolf (NaC2H3O2.3H2O), Mechlich (HCl 0.05N + H2SO4 0.025N) dan NH4OAc (NH4OAc, pH 7). The results showed differences in response of plant height and biomass dry weight on nutrient status of Andisols P. Quandratic response pattern was shown in tomato plant height at 7 weeks after planting and biomass dry weight. The best Andisols P extraction method for tomato is Morgan Wolf, with a correlation coefficient (r) was 0.79. Keywords: biomass, extraction method, greenhouse, H3PO4, Morgan Wolf